A long-lasting prolactin stimulates galactopoiesis in mice - Kasia Kready; Kailyn E. Doiron; Katherine Redfield Chan; Jeffrey C. Way; Quincey Justman; Camille E. Powe; Pamela A. Silver (iScience)
Summary: Prolactin is the main hormonal driver of mammalian lactation. To sustain milk production, basal prolactin levels must remain elevated compared to nonpregnant states. However, prolactin (23 kDa) is short-lived in circulation due to rapid renal excretion. Here, we design and test the galactopoietic effects of an engineered long-lasting prolactin in mice. The engineered variant, prolactin-extra long-acting (Prolactin-XL), is comprised of endogenously active human prolactin fused to an engineered human immunoglobulin G1 (IgG1) Fc domain. Prolactin-XL has a serum half-life of 70.9 h in mice, 2,625-fold longer than endogenously active human prolactin alone (70.9 h vs. 0.02 h). Prolactin-XL is engineered to be more susceptible to gastrointestinal proteases to reduce its uptake by nursing neonates. We demonstrate that Prolactin-XL increases lactation and restores growth of pups fed by dams with pharmacologically ablated lactation. We propose that Prolactin-XL is a potential tool for the study and pharmacologic stimulation of galactopoiesis.